A decomposition based metaheuristic approach for solving rapid needs assessment routing problem. (September 2021) - Mıhçıoğlu, Yurtsev; Albey, Erinç
Highlights: Obtaining high-quality solutions expeditiously is crucial in humanitarian problems. Proposed decomposition algorithm helps to attack each sub-problem efficiently. Designed algorithm is better (time & solution quality wise) compared to benchmarks. Algorithm's modular structure allows possible future modifications by researchers. Abstract: This paper proposes a decomposition based tabu search algorithm for solving multi-cover routing problem in the case of rapid need assessment. Rapid needs assessment aims to evaluate impact of a disaster at different sites to determine the needs of different community groups. Since the assessment process during a disaster is time critical, the focus in this paper is given to developing a solution approach, which aims to find high quality solutions in short period of time. The proposed algorithm focuses on a three-stage decomposition, where stages involve site selection, team assignment and routing of teams. Performance of the proposed algorithm is evaluated with respect to benchmark algorithms under different instances. The results indicate that the proposed algorithm can achieve high-quality solutions expeditiously, providing better results, on the average, when compared to the best-known solution approaches in the literature.